Analisis Data Batimetri untuk Penentuan Alur Pelayaran Sungai Kapuas Desa Balai Belungai Kabupaten Sanggau - Muqsit J.A, Ibrahim; Zulfian, Zulfian; Putra, Yoga Satria (Universitas Islam Negeri Alauddin Makassar, 2025)
The Kapuas River is a river located in West Kalimantan. Especially in Balai Blungai Village, Toba District, Sanggau Regency, this area has an important role in the distribution of goods and the mobility of barges carrying sand and bauxite to the Kapuas estuary. The depth of the river can be determined based on bathymetry data. Bathymetry is a measure of the height and low contour of the water base (depth). The purpose of this study was to determine the variation in river depth and determine recommendations for transportation routes on the Kapuas River channel, Balai Belungai Village, Toba District, Sanggau Regency based on bathymetry data. The research method used is the interpolation method used for bathymetry refinement is the triangulation with linear interpolation method by calculating the value of a point against three points that have the closest distance so that in the end the depth contour value is obtained. The tracks for barymetric data parallel to the river are 3 tracks with a track length of 2.7 km to 4.5 km and 6 tracks intersect the three tracks with a track length of 906 m to 971 m. The distance between measurement points is 3 m. The results of the study showed that the bathymetry and current in the Kapuas River, Balai Belungi Village, Toba District, Sanggau Regency vary, with depths between -2 m to -10 m and surface currents of 1.31 m / s to 2.40 m. The recommended shipping lane for loaded ships and barges is at a depth of -5 m to -10 m, with a shipping lane width of 200 m to 500 m.